2018
DOI: 10.1007/s11418-018-1204-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-invasive effect of Cyclamen pseudibericum extract on A549 non-small cell lung carcinoma cells via inhibition of ZEB1 mediated by miR-200c

Abstract: Scientists are increasingly focusing attention on natural products of plant origin for use as agents in cancer protection and treatment. Cyclamen L. tuber extracts contain saponin glycosides that have been shown to have anti-cancer and other biological activities. The epithelial-to-mesenchymal transition (EMT) is thought to enhance malignant tumour progress. The transcriptional repressor zinc-finger E-box binding homeobox 1 (ZEB1) is an important inducer of EMT in different human tumours and has recently been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Therefore, we may not compare our results with aforementioned literature data which found low cytotoxic activity or absense of it in C. hederifolium from Turkey [9,12] . Our results are however in accordance with other studies that point out the significant antitumor effects of Cyclamen spp found on different cell lines [8,34,38,39] .…”
Section: Antioxidant Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, we may not compare our results with aforementioned literature data which found low cytotoxic activity or absense of it in C. hederifolium from Turkey [9,12] . Our results are however in accordance with other studies that point out the significant antitumor effects of Cyclamen spp found on different cell lines [8,34,38,39] .…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…trochopteranthum against hepatocelular (HepG2) and colorectal adenocarcinoma (Caco-2) cell lines, while C. pseudibericum exhibited activity against non-small cell lung carcinoma cells (A549) [38,39] . Although strong cytotoxic effect was oberved in investigation of C. to the extracts of these plants, since the experiments were performed with isolated and purified secondary metabolites (saponins) [8] .…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Karagur et al demonstrated that the high expression of miR-200 could reduce the expression of N-cadherin and vimentin by increasing the expression of E-cadherin and targeting ZEB1 to inhibit the ZEB1. EMT is considered to be an initiator of tumor malignancy and miR-200 was capable of impeding the EMT of NSCLC A549 cell line (30). Thus, we wondered whether the increase of aberrant expression for UbcH10 in NSCLC tissues and cells was caused by the inactivation of miRNA regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Still in NSCLC cell lines, Cyclamen pseudibericum Hildebr. extract up-regulated miR-200c which, in turn, targeted the transcriptional repressor Zinc finger E-box-binding homeobox 1 (ZEB1), resulting in decreased expression of E-cadherin, N-cadherin and vimentin, reflecting the EMT-inhibitory properties of this extract ( Karagur et al, 2018 ).…”
Section: Terpenoids and Meroterpenoidsmentioning
confidence: 99%